La Junta General de Caciques en el Fütawillimapu, 1936-1985 - Alejandro Cárcamo Mansilla (Les Cahiers ALHIM)
The Junta General de Caciques is a Mapuche-Williche organization that dates back to 1793, when the Treaty of Las Canoas was signed with the Spanish, but as such it appeared in 1936. This organization, the legitimate representative of the Mapuche-Williche, between 1936 and 1985, under the representation of their Apo Ülmen or chiefs and grassroots leaders, called for assemblies and wrote memorials with demands that it delivered to the governments of the Chilean state in the period of study. Through the description of the demands appearing in the memorials, we will be able to see the Mapuche-Williche autonomist demand over a certain space such as the historical territory of the Mapuche-Williche, the Fütawillimapu.